Financing on-the-job training: Shared investment or promotion based system? - Pannenberg, Markus [Verfasser] (My University, 1997)
"Though the shared investment hypothesis of human capital theory, i.e. that employers and employees share the costs of and the return on investment in firm-specific human capital, is widely accepted, we know little about the empirical evidence. The paper shows that in German data (1984-1991) there is no empirical evidence for the shared investment hypothesis. Rather we observe that employers are able to protect one-sided investments against opportunistic bargaining. Moreover there is a positive correlation between the incidence of employer-supported on-the-job training and promotions within firms." (author-s abstract, IAB-Doku)((en)) "Obwohl Beckers "shared investment" Hypothese der Teilung der Kosten und der Quasi-Rente von Investitionen in firmenspezifisches Humankapital arbeitsmarktökonomisches Allgemeingut ist, wissen wir wenig über ihre empirische Evidenz. Die Arbeit zeigt mit Daten des Sozio-ökonomischen Panels 1984-91, dass Beckers Hypothese für die Bundesrepublik keine Bedeutung besitzt. Vielmehr ist die betriebliche Personalpolitik bei einseitiger Finanzierung in der Lage, die Investition gegen opportunistisches Verhalten zu sichern. Darüber hinaus findet sich ein positiver Zusammenhang von arbeitgeberseitig (mit-)finanzierten Weiterbildungsinvestitionen und Beförderungen in der jeweiligen Firma." (Autorenreferat, IAB-Doku)
Keywords: S 4.3.6 Human Capital; S 5.3 Personalentwicklung; G 1.3.1.2 Weiterbildungsmarkt; L 2.1.3 Erfahrungslernen; L 2.1.1 Informelles Lernen; S 4 Kosten & Finanzierung; G 1.2.2.1 Lohn- & Tarifsysteme; Humankapitalansatz; Betriebliche Weiterbildung; On-the-job training; Berufliche Weiterbildung; Finanzierung; Beförderung; Quantitative Angaben; 1984-1991